3M syndrome in Saudi Arabia: a case series study and literature review - Alhuthil, Raghad; Alsagheir, Afaf; Almslam, Maha; Raed, Jana; Barakat, Farah; Murad, Sarah; Bin-Abbas, Bassam (Frontiers in Endocrinology, 2025)
Background3M syndrome (3MS) is a very rare autosomal recessive disorder characterized by short stature, distinctive facial features, and skeletal abnormalities. The condition is frequently underdiagnosed due to its nonspecific symptoms and normal neurocognitive development. Few reports exist on its clinical course and response to growth hormone (GH) therapy. Therefore, this study aims to describe the clinical features of Saudi patients with 3MS and to investigate the effects of growth hormone therapy on growth.MethodsWe conducted a retrospective case series of 14 Saudi patients from 11 families with genetically confirmed 3MS at King Faisal Specialist Hospital and Research Centre in Riyadh.ResultsThe mean age at diagnosis was 5.4 years. Consanguinity was present in 79% of cases. The most frequently affected gene was CUL7 (57% of cases), followed by OBSL1 and CCDC8. All variants were predominantly homozygous and classified as pathogenic or likely pathogenic. Clinical abnormalities included growth retardation, dental abnormalities, spinal abnormalities, and a characteristic facial appearance. GH therapy was administered to 10 children; 5 demonstrated a measurable improvement in growth velocity, while 5 did not respond or discontinued treatment. IGF-1 was within/low-normal in most tested cases, with two elevated results.ConclusionOur study highlights the extensive phenotypic variability of 3MS and underscores the predominantly autosomal recessive inheritance pattern in this population. GH therapy may provide a growth benefit in select cases, although resistance and poor response remain a challenge. Genetic testing is crucial for accurate diagnosis, individualized management, and appropriate family counseling.